Al-quran sebagai landasan dalam manajemen pendidikan islam - Maulana, Muhammad Ricky (Maliki Interdisciplinary Journal, 2026)
From an Islamic perspective, education is an effort to enable humans to recognize and acknowledge God's position in their lives. To realize the goals of education, management is necessary within an educational institution, whether general or Islamic. Management can be understood as the process of organizing and utilizing organizational resources through collaboration among members so that goals can be achieved effectively and efficiently. Meanwhile, Islamic educational management means managing others within an educational institution based on Islamic values, so that the goals of Islamic education can be optimally achieved. In educational institutions, management has several important functions that significantly influence the institution's success in achieving its vision and mission. These functions include planning, organizing, implementing, and supervising. Each function has a distinct definition and role, but they are interrelated and inseparable, as they all form a unified whole that supports the achievement of educational goals.